Study on the effect of plant hormones and pre-chilled treatment to break dormancy and germination of Rhodiola rosea seeds - WANG Qiang; RUAN Xiao; YAN QI-Chuan (浙江大学学报. 农业与生命科学版, 2005)
Rhodiola rosea has been widely used as traditional herb medicine in China for centuries. Its seeds germinate unevenly and at a low rate; this is due to dormancy of the seed. We use pre-chill treatment and exogenous plant hormones stimulation to break dormancy of Rhodiola rosea seeds, to trigger seed germination and to gain high quality seedlings; as well as to research the physiological interactions between exogenous stimulation, endogenous plant hormone change, the germination of seeds and growth of seedling. It is observed that seeds pre-chilled at 4℃ for three weeks should the highest germination rate at 25-10 ℃, the rates of germination get to (48±2)%. From our research, we found that in the embryos of seeds of Rhodiola rosea the endogenous level of ABA decreased and then maintained at low level after being treated with exogenous GA3, 2,4-D and GA3+2,4-D. Medium level of endogenous IAA (from 611.8 ng/gFW to 494.6 ng/gFW) can balance the growth of root and shoot, endogenous IAA content change at this range, the survival rate of seedling is the highest.